ANALYTICAL REASONS FOR THE HEAT LOSS ACCOMPANYING THE HEAT SUPPLY THROUGH HEAT NETWORKS (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
At present, heat supply is characterised by high consumption of heat by consumers and high heat losses in distribution systems. The heat losses in heat networks represent the issue that is currently seriously discussed, especially by distributors of heat and hot water. Heat loss in a pipeline system depends on a number of factors, such as the medium temperature, external air temperature, heat network type and length, and the thickness and quality of the used insulation. They may be identified applying two existing approaches: the experimental (using the balance method) or the analytical.